Bicaubittacus, a new genus of the Oriental Bittacidae (Mecoptera) with descriptions of two new species - Tan, Jiang-Li; Hua, Bao-Zhen (Zootaxa, 2009)
Bicaubittacus gen. nov., the second genus of the family Bittacidae from the Oriental Region, is erected with Bittacus appendiculatus Esben-Petersen, 1927 as its type species. A key to the 17 extant genera of Bittacidae is compiled to include the new genus. Two new species, Bicaubittacus yangi sp. nov. and Bi. mengyangicus sp. nov. are described and illustrated from China. Three new combinations, Bicaubittacus appendiculatus (Esben-Petersen, 1927) and Bi. longiprocessus (Huang & Hua, 2005) from China, and Bi. burmanus (Tjeder, 1974) from Myanmar (formerly Burma), are transferred from the genus Bittacus Latreille. A key to the five species of Bicaubittacus is provided. The validity of Neobittacus and Thyridates is briefly discussed